Synthesis and Characterization of Zn(II), Cu(II), and Ni(II)-Levofloxacin Complexes for Carbon Dioxide Storage Media - Hadeel Adil; Hamsa Thamer; Dina Saadi Ahmed; Raghda Alsayed; Muna Bufaroosha; Khalid Zainulabdeen; Hassan Hashim; Alaa Mohammed; Emad Yousif (Indonesian Journal of Chemistry, 2023)
Three complexes ([CuL2(H2O)2], [NiL2(H2O)2], and [ZnL2Cl2]) have been synthesized through the reaction of metal salts and levofloxacin and characterized by spectrophotometers. The morphology of the complexes was investigated using field emission scanning electron microscopy (FESEM). The physicochemical properties of these complexes were evaluated using the Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) techniques. Furthermore, the storage capacity of these complexes was verified using the H-sorb 2600 analyzer at a temperature of 323 K and varying pressure conditions. The obtained data substantiates that the synthesized complexes exhibit favorable attributes for CO2 absorption. The surface area reaches 24.97 m2/g with capacities of 123.073 m3/g and 34.400 m3/g to adsorb CO2. The escalating levels of CO2 in the atmosphere, primarily resulting from the combustion of fossil fuels to meet the surging energy requirements, pose a pressing environmental challenge. Consequently, there has been a surge in research focused on the development of novel materials aimed at facilitating CO2 storage.